On the polemic of academic integrity in higher education - Waghid, Y.; Davids, N. (South African Journal of Higher Education, 2019)
Academic integrity is integral to credible scholarship. Yet, the escalation of publications and the desire to publish, even in this journal – South African Journal of Higher Education – often bring into play the important practice of academic integrity. As the rush for publications increasingly becomes an obsession, rather than an intrinsically loved scholarly activity, the ugly side of academic fraud, cheating and plagiarism begins to accelerate, and this manifests in research outputs. This introductory article takes a critical look at three significant developments in realising research outputs in higher education: Turnitin for turnitout, academic cheating and Google cutting and pasting. We proffer what academics should be doing to avoid the malaise creeping into and manifesting in higher education.